The evolution of foreign residents in Spain - Manuel Pérez (Migraciones, 2014)
The presence of foreign population in Spain has become a reality in Spanish life from the beginning of the nineties till now. The article divides this period of almost fifteen years in three stages, first from 1990 to 1995, second from 1995 to 2000, and the last from 2000 to now. The analysis that is carried out in this article wants to explain which have been the causes that have influenced the current shape of the foreign population in Spain, the starting point being that there are causes linked to this complex phenomenon that are not determined by the Spanish internal decisions.